A new study of multi-phase mass and heat transfer in natural gas hydrate reservoir with an embedded discrete fracture model - Cui, Yudong; Teng, Bailu; Luo, Wanjing; Lu, Cheng; Zhou, Yingfang (Frontiers in Earth Science, 2023)
Studies of the hydrate cores have shown that natural fractures can be frequently observed in hydrate reservoirs, resulting in a fracture-filled hydrate. Therefore, it is highly necessary for industries to predict the gas well productivity of hydrate reservoirs with natural fractures to optimize the developing strategies. In this work, an embedded discrete fracture model is applied to characterize the natural fractures of fracture-filled gas-hydrate reservoirs. The nonlinear mass and energy conservation equations which are discretized with the finite-difference method are solved by the fully implicit approach. The proposed model is justified by comparing the calculated results to the results from a commercial simulator. On the basis of the proposed model, we investigate the influences of natural fractures, fracture conductivity, and hydrate dissociation rate on the gas well productivity and the distributions of pressure, temperature, and hydrate saturation. The simulation results show that hydraulic and natural fractures exert significant impacts on the gas well productivity of the fracture-filled hydrate reservoirs, and the gas well productivity is increased as the increasing hydraulic and natural fracture conductivity. A higher hydraulic fracture conductivity can be more favorable than a higher natural fracture conductivity for improving the gas well productivity in a fracture-filled hydrate reservoir. The connected natural fractures can impose a more important influence on the gas well productivity than the unconnected natural fractures. In addition, the gas well productivity and heat transfer of fracture-filled hydrate reservoirs are significantly affected by hydrate decomposition. A higher hydrate dissociation rate can lead to a lower temperature along fractures due to a more noticeable reduction of solid hydrate.